Disruptive mood dysregulation disorder, parental stress, and attachment styles - Coldevin, Marit; Brænden, Astrid; Zeiner, Pål; Øyen, Anne-Siri; Melinder, Annika; Stubberud, Jan E. (Frontiers in Child and Adolescent Psychiatry, 2024)
Disruptive Mood Dysregulation Disorder (DMDD) is a relatively new diagnostic entity concerning children with chronic irritability and severe anger outbursts. There is so far limited knowledge about parental factors associated with the disorder. The aim of this study was to investigate parental stress levels and attachment styles in parents of children with DMDD compared to parents of children with other diagnoses. Our sample concist of 218 children (6–12 years, Mage = 9.68 years ) referred to child mental health out-patient clinics. Clinicians administered a standardized semi-structured diagnostic interview to identify diagnoses. Parental stress levels and attachement styles was assessed by parent-reports. We found that parents of children with DMDD experience significantly higher levels of parenting stress related to factors in the child than parents of children with other diagnoses. Furthermore, parents of children with DMDD show a higher association with insecure adult attachment styles than parents of children without DMDD. Lastly, adult preoccupied-ambivalent attachment style explains the variability in parental stress in the DMDD group to a large degree. We dicuss how parental stress and insecure attachment style can be associated with negative parenting practices. An implication from this study could be that treatment results might be enhanced by involving parents to a larger degree in treatment programs for children with DMDD.